The role of individual audit partners for narrative disclosures - Christoph Mauritz; Martin Nienhaus; Christopher Oehler (Review of Accounting Studies, 2021)
We analyze the extent to which individual audit partners influence the audited narrative disclosures in their clients' financial reports. Using a sample of 3,281,423 private and public client firm-pairs, we find that the similarity among audited narrative disclosures is higher when two client firms share the same audit partner. Specifically, we find that the wording similarity of management reports (notes) increases by 30 (48) percent, the content similarity by 29 (49) percent, and the structure similarity by 48 (121) percent. Moreover, we find that audit partners in particular are relevant for their clients' narrative disclosures because the increase in narrative disclosure similarity when sharing the same audit partner is nine (four) times greater than when sharing the same audit firm (audit office). We show that this influence of audit partners goes beyond adding boilerplate statements and, using novel field evidence, we shed light on the underlying mechanisms. Our findings are economically relevant because a stronger involvement of audit partners with their clients' narratives is associated with a higher quality of narrative disclosures, which helps users better predict the future profitability of client firms.
Keywords: M38; M42; 650; Narrative disclosures; Audit partner style; Production of disclosures; Textual similarity